Flux method growth of bulk MoS2 single crystals and their application as a saturable absorber1. Issue 21 (7th June 2015) - Zhang, Xixia; Lou, Fei; Li, Chunlong; Zhang, Xiang; Jia, Ning; Yu, Tongtong; He, Jingliang; Zhang, Baitao; Xia, Haibing; Wang, Shanpeng; Tao, Xutang
<x xml:space="preserve">Abstract</x> A 3 mm × 5 mm crystal of MoS2 is grown by the Sn flux method.